Personality Traits and Their Relationship with Volunteering Motivation among Students Participating in Volunteer Activities at Yarmouk University - Ali, Farah Mamoun; Al-Frehat, Basem Mohammed; Almomani, Khozama Jehad (Dirasat: Educational Sciences, 2024)
Objectives: This study aimed to explore personality traits and their relationship with volunteering motivation among students participating in volunteer activities at Yarmouk University, and to determine whether there are statistically significant differences based on sex and faculty. Method: The study utilized a descriptive correlational approach, employing both a personality traits scale and a volunteering motivation scale on a sample of 367 students selected through convenience sampling. Results: The results indicated that volunteering motivation was at a high level, with no significant differences across all dimensions based on the variables of faculty and sex, except in the humanitarian interest’s domain, which favored females. In addition, personality traits ranged from moderate to high levels, with the openness domain ranking highest and the neuroticism domain ranking lowest. There were no significant differences in personality traits across all domains based on the variables of sex and faculty, except in the neuroticism and openness domains, which favored scientific faculties. There was a negative statistical correlation between neuroticism and volunteering motivation, and a positive statistical correlation between volunteering motivation and the traits of openness, extraversion, agreeableness, and conscientiousness among students participating in volunteering activities at Yarmouk University. Conclusion: Based on these findings, the researchers emphasize the need to organize webinars on the benefits of participating in volunteer activities such as developing personal and social skills, promoting a sense of belonging, and contributing to the community.